401 Conventional Aortic Valves Versus Rapidly Deployed Valves in The Elderly Population. A Comparative Study in A Single Centre Experience. (12th October 2021) - Moawad, N; McCrorie, A; Aljanadi, F; Jones, M
Abstract: Aim: Current recommendations favour TAVI over Surgical Aortic valve replacement (SAVR) for patients aged>75 years. However, in current practice a significant proportion of patients in this group are offered SAVR. Rapidly deployed valves are of increasing popularity among surgeons as they shorten the procedure time, but their benefits are yet to be investigated. Method: Patients aged >75 years undergoing Aortic valve replacement with or without any concomitant procedure were included between January 2014 and January 2020 (total: 597). Patients were divided into two groups: Group A (495 patients) conventional Aortic valve and Group2 (102 patients) rapidly deployed valve. Results: Preoperative variables including mean age, EuroScore II, and body mass index were of no statistical significance between the two groups. More females and Octogenarians were in the rapidly deployed valve group versus the conventional valve group, respectively. Bypass time and Cross-clamp times were shorter in rapidly deployed group. However, the length of ICU and hospital stay was not significant between the two groups. Early post-operative pacemaker implantation (Conventional 2% Vs RDV 7%) (P < 0.05) differed significantly between groups. At follow up echocardiography, pressure gradients were comparable between groups. Thirty-day mortality and valve-related complications were insignificant. Conclusions: RDVs show comparable early and medium-term outcomes and valve hemodynamics. RDVs are associated with shortened operative time and cross-clamp time but may carry an increased risk of need for permanent pacing.